Determinants of Urban Young Unemployment Status and Rural in Indonesia 2012-2016 - Putra, Maulana Eka (Jurnal Ilmu Ekonomi Terapan, 2018)
In some countries, especially developing countries like Indonesia, the issue of unemployment is still the main problems for the growth and development of countries, especially unemployment a young age. In addition, the ratio of unemployed young age is dominated in urban areas than rural areas. The studies were conducted to analyze the factors that affect unemployed urban and rural areas in Indonesia in the years 2012-2016. The factor is the ratio of Male of Female, Dummy Area, Education, The Household, GDP, the level of Wages, Population, and inflation.The samples used in this study is a secondary the publication by the central statistics agency (BPS) which is then analyzed using the method of Regresi Linier Panel Data with Random Effect Model (REM) of software Eviews 9.This research result indicates that on the model unemployment in urban variable ratio of Male of Female has negative not significant, variable Dummy Area has positive significan,variable Education has positive significant, variable Household has negative not significant, variable GDP has positive significant, variable the level of Wages has negative significant, variables Population has positive not significantly, and variable inflation has negative not significant. As for the unemployed rural variable ratio of Male of Female has negative not significant, and variable inflation has negative not significant.